No increased suggestibility to placebo in functional neurological disorder. (26th March 2021) - Huys, Anne‐Catherine M. L.; Beck, Brianna; Haggard, Patrick; Bhatia, Kailash P.; Edwards, Mark J.
Abstract: Background and purpose: On the basis of occasional strong placebo responses, increased susceptibility to placebo has been proposed as a characteristic of functional neurological disorder (FND). The aim of this study was to clarify whether people with FND have a stronger placebo analgesic response than healthy controls. Methods: A study using a classic placebo paradigm, with additional conditioning and open‐label components, was performed in 30 patients with FND, and in 30 healthy controls. Ratings of mildly to moderately painful electrotactile stimuli were compared before and after the application of a placebo "anaesthetic" cream versus a control cream, after an additional conditioning exposure, and after full disclosure (open‐label component). Results: Pain intensity ratings at the placebo compared to the control site were similarly reduced in both groups. The conditioning exposure had no additional effect. After placebo disclosure a residual analgesic effect remained. Conclusion: Patients with FND did not have stronger placebo responses than healthy controls. The notion of generally increased suggestibility or increased suggestibility to placebo in FND seems mistaken. Instead, occasional dramatic placebo responses may occur because functional symptoms are inherently more changeable than those due to organic disease. Abstract : Although dramatic placebo responses occasionally occur in functional neurological disorder (FND), the susceptibility to placebo per se was not enhanced in a relatively large group of people with FND compared to healthy controls. The common notion of hypersuggestibility to placebo in this condition therefore needs to be challenged. Instead, occasional dramatic placebo effects might occur because functional symptoms are inherently more changeable than organic symptoms.